Integrasi Artificial Intelligence dalam Perencanaan Pembelajaran: Tinjauan Konseptual Literasi Digital dan Kesiapan Guru PAI - Angga Saputra; Kurniawati Rahmah (Institut Kariman Wirayudha Sumenep, 2026)
Digital transformation through Artificial Intelligence (AI) innovation requires educators to be prepared to adapt their instructional strategies, particularly in Islamic Religious Education (IRE). This study aims to analyze the conceptual relationship between digital literacy, technological support, and the readiness of IRE teachers to integrate AI into lesson planning. Using a library research method with a descriptive-qualitative approach, a content analysis was conducted on 17 selected reputable scientific literatures published between 2021 and 2026. The results indicate that digital literacy serves as a cognitive foundation influencing teachers' self-confidence; however, critical literacy is urgently needed to validate AI outputs. Furthermore, technological infrastructure and institutional policies act as vital catalysts. The novelty of this study highlights that while AI enhances administrative efficiency in compiling lesson plans, the IRE teacher's role must evolve into a moral curator and pedagogical validator to ensure alignment with Islamic values. In conclusion, a synergy between individual digital competence and structural technological support is paramount.